Duties and Responsibilities of the Principal in Madrasa towards Teachers’ Professionalism Development - Totok Sudarmanto; Abd. Muis; Mundir Mundir; Zainal Abidin (JIEMAN: Journal of Islamic Educational Management, 2022)
The purpose of this study was to describe the role of the principal as a leader and manager in developing teacher professionalism. This research uses a case study approach. Data was obtained by observation, interviews, and document review. Data analysis used interactive analysis consisting of data reduction, data presentation, and conclusions. This research resulted in three findings. First, as the innovator, duties and responsibilities of madrasah principals are enriching insight and related information about madrasa, opening a new madrasa program, restructuring madrasah, conducting reinforcement, developing the professionalism of teachers individually and in teams, managing the physical environment, and performing alternation. Second, as the motivator, duties and responsibilities of madrasa principals are provide a spiritual approach, apply the motto of ki hadjar dewantara motto "ing ngarso sung tulodho, ing madya mangun karso, tut wuri handayani, encourage teachers to improve their educational qualifications, provide rewards, initiate discipline, strengthen the friendship, and improve teacher welfare, provide recreation, pay attention to subordinates' conditions, and resolve conflicts. Third, as the administrator, duties and responsibilities of the madrasa principals are constructing job description and job specifications, constructing job description and job specifications, allocating all of the resources in the madrasa, assigning a capable person to lead a group of people, coordinating the performance of teachers and staff within madrasa, arranging program scheduling in madrasa, collaborating with other parties. Tujuan penelitian ini adalah untuk mendeskripsikan peran kepala sekolah sebagai pemimpin dan manajer dalam mengembangkan profesionalisme guru. Penelitian ini menggunakan pendekatan studi kasus. Data diperoleh dengan observasi, wawancara, dan telaah dokumen. Analisis data menggunakan analisis interaktif yang terdiri dari reduksi data, penyajian data, dan penarikan kesimpulan. Penelitian ini menghasilkan tiga temuan. Pertama, sebagai inovator, tugas dan tanggung jawab kepala madrasah adalah untuk menambah wawasan dan informasi terkait madrasah, membuka program madrasah baru, restrukturisasi madrasah, melakukan penguatan, mengembangkan profesionalisme guru secara individu maupun tim, dan mengelola lingkungan fisik, melakukan pergantian. Kedua, sebagai motivator, tugas dan tanggung jawab kepala madrasah adalah untuk memberikan pendekatan spiritual, menerapkan semboyan Ki Hadjar Dewantara “Ing ngarso sung tulodho, ing madya mangun karso, tut wuri handayani, mendorong guru untuk meningkatkan kualifikasi pendidikannya, memberikan penghargaan, memprakarsai disiplin, mempererat silaturrahmi, dan meningkatkan kesejahteraan guru, memberikan rekreasi, memperhatikan kondisi bawahan, dan menyelesaikan konflik.  Ketiga, sebagai administrator, tugas dan tanggung jawab kepala madrasah adalah membuat deskripsi pekerjaan dan spesifikasi pekerjaan, mengalokasikan semua sumber daya yang ada di madrasah, menugaskan orang yang cakap untuk memimpin sekelompok orang, mengkoordinir kinerja guru dan staf di lingkungan madrasah, menyusun jadwal program di madrasah, dan bekerjasama dengan pihak lain.